Pemetaan Zona Rawan Banjir Berbasis Skoring dan Pembobotan di Kecamatan Balusu, Kabupaten Barru - M. Agussalim; Indriyanti Aziz; Fahril (Jurnal Karajata Engineering, 2025)
Balusu District is one of the areas in Barru Regency that has geographical characteristics that are prone to flooding. Topographically, this district has lowlands that tend to be prone to flooding during the rainy season. The purpose of this study was to determine the most dominant factors that causing flooding and to map the area of ​​flood-prone areas in Balusu District, Barru Regency. The method used in this study was to use the scoring and weighting method. The parameters of this study namely rainfall, land height, slope, soil type and land use will later be assessed by giving weights and classification values to each and then processed using the ArcGIS software. The results obtained from this study are the most dominant factors and causes of flood vulnerability in Balusu District are land elevation and high rainfall and the distribution of flood-prone areas in Balusu District is 42.68% of the total area of ​​Balusu District, which is 104.82 km².